PENDAMPINGAN BELAJAR FISIKA BERBASIS UNITY 3D BAGI SISWA SMPK REGINA PACIS - Ni Wayan Suparmi; Maria Goreti Kui; Frederikus Ngongo (LPPM Universitas Bina Bangsa, 2024)
Based on the results of interviews with SMPK teacher Regina Pacis, it is known that physics is still a subject that is considered difficult. This is proven by the low number of students who reach the KKM in each lesson. Therefore, it is a challenge for educators to be able to eliminate the impression of difficulty by using interesting learning media. Apart from that, this service is based on the problem of junior high school students who are less interested in learning physics concepts because they have difficulty connecting the concepts with real situations in the real world. The aim of this community service activity is to introduce Unity 3D and provide assistance in using Unity 3D-based physics learning media to students at SMPK Regina Pacis. Learning assistance activities using Unity 3D physics learning media aim to: (1) physics concepts developed in Unity 3D can be easily applied to relate them to the real world; 2) the connection between students' lives and the material being studied can encourage students to be more enthusiastic about the ongoing learning process so that it can foster students' love of physics. The approach method for implementing community service activities includes the lecture method and the question-and-answer method. The results of satisfaction responses to learning assistance activities show that learning assistance participants consider this learning assistance activity to be very useful and enjoyable. This learning assistance activity also provides direct experience to SMPK Regina Pacis students in using Unity 3D media to study solar system material. Apart from that, the tutoring participants are very enthusiastic and actively interact with the tutors during the learning process and the use of this media can improve the participants' understanding of the material